2015
DOI: 10.1111/jeb.12552
|View full text |Cite
|
Sign up to set email alerts
|

Connecting thermal performance curve variation to the genotype: a multivariate QTL approach

Abstract: Thermal performance curves (TPCs) are continuous reaction norms that describe the relationship between organismal performance and temperature and are useful for understanding trade-offs involved in thermal adaptation. Although thermal trade-offs such as those between generalists and specialists or between hot- and cold-adapted phenotypes are known to be genetically variable and evolve during thermal adaptation, little is known of the genetic basis to TPCs - specifically, the loci involved and the directionalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…However, our results clearly demonstrate that TPCs are not static, but are plastic and can be influenced by thermal acclimation. Genetic variation can also likely influence TPCs (Kingsolver & Gomulkiewicz, ; Kingsolver et al, ; Knies et al, ; Latimer, Foley, & Chenoweth, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our results clearly demonstrate that TPCs are not static, but are plastic and can be influenced by thermal acclimation. Genetic variation can also likely influence TPCs (Kingsolver & Gomulkiewicz, ; Kingsolver et al, ; Knies et al, ; Latimer, Foley, & Chenoweth, ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic mapping studies of plasticity have revealed gene-by-environment interactions for life history traits in diverse organisms, including C. briggsae ’s nematode cousin C. elegans (Vieira et al 2000; Ungerer et al 2003; Hausmann et al 2005; Gutteling et al 2007). However, analysis of Drosophila serrata locomotory activity in thermal performance curves from natural variation (Latimer et al 2011), QTL mapping with RILs (Latimer et al 2015), and via mutation accumulation (Latimer et al 2014) provides an especially useful comparison to our work on C. briggsae . Like our analysis for C. briggsae , Latimer and colleagues’ data did not support the “hotter is better” hypothesis, instead suggesting that tropical genotypes of D. serrata were more specialized, with a higher peak performance and narrower TPC than other natural populations.…”
Section: Discussionmentioning
confidence: 99%
“…A single further generation of full-sib inbreeding was applied before extraction of DNA. This same inbred line was used for the D. serrata linkage map, was the founding line for previous mutation accumulation studies (Latimer et al 2015; McGuigan et al 2011a, 2014a,b), and is fixed for the light female abdominal pigmentation phenotype mapped by Yassin et al (2016). High molecular weight DNA was extracted from fly bodies (heads were excluded to reduce eye pigment contamination) using a QIAGEN Gentra Puregene Tissue Kit (Cat #158667), which produced fragments > 100 kbp (measured using pulsed-field gel electrophoresis).…”
Section: Methodsmentioning
confidence: 99%